Epigenetic Reprogramming Induced Pluripotency - Anna Meiliana; Andi Wijaya (The Indonesian Biomedical Journal, 2011)
BACKGROUND: The ability to reprogram mature cells to an embryonic-like state by nuclear transfer or by inducing the expression of key transcription factors has provided us with critical opportunities to linearly map the epigenetic parameters that are essential for attaining pluripotency.CONTENT: Epigenetic reprogramming describes a switch in gene expression of one kind of cell to that of another unrelated cell type. Early studies in frog cloning provided some of the first experimental evidence for reprogramming. Subsequent procedures included mammalian somatic cell nuclear transfer, cell fusion, induction of pluripotency by ectopic gene expression, and direct reprogramming. Through these methods it becomes possible to derive one kind of specialized cell (such as a brain cell) from another, more accessible tissue, such as skin in the same individual. This has potential applications for cell replacement without the immunosuppression treatments commonly required when cells are transferred between genetically different individuals.SUMMARY: Reprogramming with transcription factors offers tremendous promise for the future development of patient-specific pluripotent cells and for studies of human disease. The identification of optimized protocols for the differentiation of iPS cells and ES cells into multiple functional cell types in vitro and their proper engraftment in vivo will be challenged in the coming years. Given that the first small molecule approaches aimed at activating pluripotency genes have already been devised and that murine iPS cells have recently been derived by using non-integrative transient expression strategies of the reprogramming factors, we expect that human iPS cells without permanent genetic alterations will soon be generated.KEYWORDS: epigenetics, reprogramming, pluripotency, stem cells, iPS cells, chromatin, DNA methylation